ANALISIS MUATAN PROFIL PELAJAR PANCASILA PADA TEKS CERITA “SUKA DAN TIDAK SUKA” PADA BUKU PEMBELAJARAN BAHASA INDONESIA KELAS IV SD NEGERI BABADSARI KEBUMEN - Fatoni, Muhamad; Suyoto; Muflikhul Khaq (Cerdas Proklamator, 2023)
This research was motivated by the difficulty of knowing the content of the profile of Pancasila students in the story text entitled "Likes and Dislikes". This research aims to find out what the profile of Pancasila students contains in the story text "Likes and Dislikes" in the fourth grade Indonesian language learning book at Babadsari State Elementary School. This research uses descriptive qualitative methods. The results of this research are that there are five contents of the profile of Pancasila students in the story text "Likes and Dislikes" in the Indonesian language learning book, namely 1) The dimension of faith, devotion to God Almighty and having noble morals, elements of morals towards humans are contained in the eighth paragraph, line sixth from the bottom. 2) The critical reasoning dimension, the element of obtaining and processing information and ideas, is contained in the fourth paragraph, eleventh line from the top. 3) The independent dimension of elements of self-understanding and the situation faced is contained in the fifth paragraph, fifteenth line from the top. 4) The creative dimension of the element of producing original work and actions is contained in the third paragraph, eighth line from the top and the element of having flexibility of thinking in finding alternative solutions to problems is contained in the nineteenth paragraph, third line from the bottom. 5) The mutual cooperation dimension of the sharing element is contained in the seventeenth paragraph, ninth line from the bottom.